Thoracic intradural extramedullary lesions causing progressive myelopathy as an initial manifestation of granulomatosis with polyangiitis: a case report and review of literature. (2nd January 2017) - Taniguchi, Yuki; Chikuda, Hirotaka; Oshima, Yasushi; Ohya, Junichi; Matsubayashi, Yoshitaka; Morikawa, Teppei; Shirai, Harumi; Sasaki, Oh; Shibuya, Mihoko; Fujio, Keishi; Yamamoto, Kazuhiko; Tanaka, Sakae
Abstract : Context : To our knowledge, only a few reports regarding the spinal involvement of granulomatosis with polyangiitis (GPA)—also termed as Wegener's granulomatosis—have been published. However, all these cases reportedly exhibited epidural tumor-like lesions or dural thickening. Findings : We report the case of a 57-year-old woman with progressive myelopathy caused by multiple spinal lesions with GPA, which appeared to be protruding inwards, within the dura mater, on magnetic resonance imaging (MRI); these lesions were difficult to distinguish from intradural tumors. Moreover, these lesions exhibited low intensity on both T1- and T2-weighted MRI, and showed prominent enhancement on gadolinium-contrast imaging. Resection biopsy was effective for both diagnosis and the recovery of the neurological deficit. Conclusion : Based on these findings, we suggest that GPA lesions can exhibit variable patterns in the spine. Nevertheless, clinicians should consider the possibility of GPA in such cases, particularly when multiple, inwardly protruding tumor-like lesions are detected within the dura mater on MRI.